2021
DOI: 10.3389/fonc.2021.603681
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3A Expression in Upper Tract Urothelial Carcinoma

Abstract: BackgroundEpidemiological studies have reported various results regarding whether FOXO3A is related to various carcinomas. However, the prognostic significance of FOXO3A in upper tract urothelial carcinoma (UTUC) remains unclear. The purpose of this study was to validate the correlation between FOXO3A expression and oncological outcomes in UTUC.MethodsThe expression levels of FOXO3A in 107 UTUC patients were examined by immunohistochemistry (IHC). We examined the prognostic role of FOXO3A by using the Cox prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Forkhead box O3A (FOXO3A), which belongs to the FOXO protein family and is located on human chromosome 6q21, is usually involved in DNA damage repair, cell cycle regulation, apoptosis, and the cell stress response as an important transcriptional regulator. Downregulation of FOXO3A expression may promote the occurrence, metastasis, and progression of UTUC [ 33 ]. François et al used targeted next-generation sequencing to prospectively sequence tumors and found a significant correlation between the risk of bladder recurrence after radical surgery for UTUC and mutations in FGFR3, KDM6A, CCND1, and TP53 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Forkhead box O3A (FOXO3A), which belongs to the FOXO protein family and is located on human chromosome 6q21, is usually involved in DNA damage repair, cell cycle regulation, apoptosis, and the cell stress response as an important transcriptional regulator. Downregulation of FOXO3A expression may promote the occurrence, metastasis, and progression of UTUC [ 33 ]. François et al used targeted next-generation sequencing to prospectively sequence tumors and found a significant correlation between the risk of bladder recurrence after radical surgery for UTUC and mutations in FGFR3, KDM6A, CCND1, and TP53 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The flowchart for study selection in this meta-analysis is presented in Figure 1. The literature retrieval process obtained 21 eligible articles, 14,15,17,19,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] encompassing 4058 cancer patients, published from 2008 to 2021. The mean of sample size was 193, ranging from 60 to 934 patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…13 Overexpression of FOXO3a is associated with poor prognosis in triple-negative breast cancer, 14 hepatocellular carcinoma, 15 glioblastoma, 16 and upper tract urothelial carcinoma. 17 IT is also correlated with unfavorable clinicopathological features such as advanced tumor node metastasis (TNM) stages, histological grades, and vessel invasion. In addition, tumors with highly expressed FOXO3a appear to be more prone to metastasis.…”
Section: Introductionmentioning
confidence: 99%